Consumer Reports of “Keto Flu” Associated With the Ketogenic Diet - Bostock, Emmanuelle C. S.; Kirkby, Kenneth C.; Taylor, Bruce V.; Hawrelak, Jason A. (Frontiers in Nutrition, 2020)
Background: The ketogenic diet (KD) is a high-fat, low-carbohydrate diet that limits glucose and results in the production of ketones by the liver and their uptake as an alternative energy source by the brain. KD is an evidence-based treatment for intractable epilepsy. KD is also self-administered, with limited evidence of efficacy, for conditions including weight loss, cognitive and memory enhancement, type II diabetes, cancer, neurological and psychiatric disorders. A commonly discussed side effect of KD in media and online forums is “keto flu”, a cluster of transient symptoms generally reported as occurring within the first few weeks of KD. This study aimed to characterize the pattern of symptoms, severity and time course of keto flu as related by users of online forums. Method: Online forums referring to “keto flu”, “keto-induction” or “keto-adaptation” in the URL were identified in Google. Passages describing personal experiences of keto flu were categorized manually with reference to pattern of symptoms, severity, time course and recommended remedies. Results: The search criteria identified 75 online forums, 43 met inclusion criteria and contained 448 posts from 300 unique users. Seventy-three made more than one post (mean 3.12, range 2-11). Descriptors of personal experience of keto flu, reported by 101 of 300 users, included 256 symptom descriptions involving 54 discrete symptoms. Commonest symptoms were ‘flu’, headache, fatigue, nausea, dizziness, ‘brain fog’, gastrointestinal discomfort, decreased energy, feeling faint and heartbeat alterations. Symptom reports peaked in the first and dwindled after four weeks. Resolution of keto flu symptoms was reported by eight users between days 3-30 (median 4.5, IQR 3-15). Severity of symptoms, reported by 60 users in 40 forums, was categorised as mild (N=15), moderate (N=23) or severe (N=22). Eighteen recommended remedies were proposed by 121 individual users in 225 comments. Conclusions: symptoms reported in online forums peaked in week 1 and resolved by week 4. Typically, individual posts provided fragmentary descriptions related to the flow of forum conversations. A composite picture emerged across 101 posts describing personally experienced symptoms. User conversations were generally supportive, sharing remedies for keto flu reflecting assumptions of physiological effects of KD.